Intraductal fully covered self-expanding metal stents in the management of post-liver transplant anastomotic strictures: a UK wide experience. (September 2022) - Ahmed, Wafaa; Kyle, Dave; Khanna, Amardeep; Devlin, John; Reffitt, David; Zeino, Zeino; Webster, George; Phillpotts, Simon; Gordon, Robert; Corbett, Gareth; Gelson, William; Nayar, Manu; et al.
Background: Fully covered intraductal self-expanding metal stents (IDSEMS) have been well described in the management of post-liver transplant (LT) anastomotic strictures (ASs). Their antimigration waists and intraductal nature make them suited for deployment across the biliary anastomosis. Objectives: We conducted a multicentre study to analyse their use and efficacy in the management of AS. Design: This was a retrospective, multicentre observational study across nine tertiary centres in the United Kingdom. Methods: Consecutive patients who underwent endoscopic retrograde cholangiopancreatography with IDSEMS insertion were analysed retrospectively. Recorded variables included patient demographics, procedural characteristics, response to therapy and follow-up data. Results: In all, 162 patients (100 males, 62%) underwent 176 episodes of IDSEMS insertion for AS. Aetiology of liver disease in this cohort included hepatocellular carcinoma ( n  = 35, 22%), followed by alcohol-related liver disease ( n  = 29, 18%), non-alcoholic steatohepatitis ( n  = 20, 12%), primary biliary cholangitis ( n  = 15, 9%), acute liver failure ( n  = 13, 8%), viral hepatitis ( n  = 13, 8%) and autoimmune hepatitis ( n  = 12, 7%). Early AS occurred in 25 (15%) cases, delayed in 32 (20%) cases and late in 95 (59%) cases. Age at transplant was 54 years (range, 12–74), and stent duration was 15 weeks (range, 3 days–78 weeks). In total, 131 (81%) had complete resolution of stricture at endoscopic re-evaluation. Stricture recurrence was observed in 13 (10%) cases, with a median of 19 weeks (range, 4–88 weeks) after stent removal. At removal, there were 21 (12%) adverse events, 5 (3%) episodes of cholangitis and 2 (1%) of pancreatitis. In 11 (6%) cases, the removal wires unravelled, and 3 (2%) stents migrated. All were removed endoscopically. Conclusion: IDSEMS appears to be safe and highly efficacious in the management of post-LT AS, with low rates of AS recurrence.